Are e-Scooters Parked Near Bus Stops? Findings from Louisville, Kentucky - Mohamed Abouelela; Christelle Al Haddad; Constantinos Antoniou (Findings)
With the increasing popularity of shared e--scooters, understanding where they are parked becomes crucial, especially for integrating them with existing public transportation services. In this study, we analyzed the relationship between trip origins and the nearest bus stops, using 506,000 shared e-scooter trips from Louisville, Kentucky. We examined this relation temporally for different hours of the day and different weekdays, but also spatially, using three metrics including land use, distance from the city center, and the Local Index of Transit Availability (LITA) accessibility index. The temporal analysis showed a different parking distance pattern during early morning hours (between 2 and 4 a.m.), whereas the spatial analysis showed no impact of spatial features on distances between scooter parking (and therefore trips starting points) and nearest bus stops.